Examining Career-Orientation Determinants of Managerial Roles in Nepal - Joshi, Surendra Prasad; Ghimire, Binod; Subedi, Sugam; Karki, Prajwal (Management Dynamics, 2023)
This study examines the factors influencing career orientations among Nepalese professionals and students. The objective is to explore the correlations between proactive personality, ambition, career self-management, mentorship relationships, commitment, and career orientations. The research uses a sample of 275 participants involved in managerial roles in different corporate houses. The study adopted descriptive and causal-comparative approaches. The major findings reveal significant positive correlations between these factors and career orientations. Regression analysis underscores the substantial predictive role of ambition (β = 0.302), career self-management (β = 0.302), and commitment (β = 0.370), indicating their significant impacts on career orientations. These insights contribute to a deeper understanding of the interplay of individual attributes and external factors in shaping career trajectories. Future research could expand geographically and adopt longitudinal perspectives to enrich these findings and recommendations for enhancing career development practices.